Manajerial Muraja'ah untuk Meningkatkan Kualitas Hafalan al Quran - Luluk Maktumah; Badrut Tamam; Shofiyah Nurfala Laili (FENOMENA, 2021)
This research is based on the problems that are commonly experienced by female tahfidz students, which are more enthusiastic about making new memorization than keeping what has been memorized, but too dense activity of students which makes it difficult for students to manage the time between a dormitory and school obligations. To maintain memorization, there is a need for a method to optimize the activities in the women's Tahfidzul Qur'an institution, the method called the muraja'ah method is very helpful for students to keep the spirit of maintaining the memorization of the Qur'an. This study aims to determine the implementation of the takrar method in improving the quality of memorizing the Qur'an at the Tahfidzul Qur'an Putri Institute of the Salafiyah Syafi'iyah Islamic Boarding School Sukorejo. The research design used is a field research method with a qualitative approach, research using interviews, observation, and documentation. Data analysis techniques are data reduction, data presentation, and drawing conclusions. The results showed that 1) Managerial muraja'ah goes through three stages, namely reciting ada' or tahsin al-Qur'an, Sima'an peers and three depositing memorizations to experts 2) Optimizing managerial muraja'ah stimulates the quality of memorizing students. The variety of muraja'ah as implemented by pentassmi' has an impact on students so they don't get bored, other optimizations carried out by the institution are providing solutions to all obstacles or obstacles experienced by students, namely bringing in motivators.